METAL BHASMAS: A POSSIBLE SOURCE OF TRACE ELEMENTS - Sushma, *Dongre; Dinesh, Kelgaonkar (International Journal of Ayurveda and Pharma Research, 2016)
Trace elements are important constituents required for normal physiological functioning. Iron, Zinc, Manganese, copper; Fluoride, Molybdenum, Chromium and selenium and Iodine are some of the trace elements required for body in very minute quantity and generally its need is fulfilled from intake of balanced diet. However the increased tendency in recent times towards unbalanced food intake, excessive purification of crops, and dieting practiced widely to reduce body weight, deficiencies of a trace elements are relatively frequent. To encounter this deficiency generally supplementation of multi mineral drugs are given. Rasaushadhies (Herbomineral preparations) could be the answer to this especially metallic Bhasmas (Incinerated minerals) as it contains various trace elements along with basic elements. Hence present paper aimed to review analytical studies conducted on Dhatu bhasma (metallic incinerated powders prepared by Ayurvedic methods) to find out important trace elements in them. For this purpose analytical studies on Saptadhatu bhasmas (Seven metallic Bhasmas) namely Suwarna (Gold), Rajat (Silver), Tambra (Copper), Louha (Iron), Vanga (Tin), Naga (Lead) and Yashada (Zinc) bhasma was reviewed. It is observed that these Bhasma preparation contain significant number important trace elements such as Iron, Manganese, Copper, Calcium etc. Also due to immune modulator and rejuvenating properties of these Bhasma preparations, Bhasma can be a possible source of trace elements. However there is need of further research on both experimental and clinical ground to find out role of administration of trace elements in the form of Bhasma in treating deficiency disorders of trace elements.